Kultura gospodarcza w układach lokalnych - Polski, Jan (Economic Culture in the Local Context, 2006)
Intensive transformations in Poland, preparation and Poland's accession to the European Union and general opening of our country towards the world are factors precipitated the process of thorough transformations in the sphere of consciousness and style of life, social and institutional structures in economic and civilization context. This process is still continued. Economic culture is important or the most important element of those transformations. Thus far this term has been used rarely in science and socio-economic policy. According to the author, it is necessary to define the essence and extent of its meaning. Nowadays one should define the term of economic culture in the following ways: 1) as a whole of achieved material and mental property of inhabitants at a given area (e.g. community or gmina), in the sphere of every economic activity; 2) as achieved level of skills in management and support of economic development; 3) as a level of intellectual development being of great relevance for the economy. Economic culture in not identical with the achieved level of socio-economic development. It does not include the state of ownership or gminas' or other areas' level of well-being. Nevertheless it is the most important component of socio-economic resources and simultaneously the factor of development and structural transformations. According to the author it is a needed term as a tool of policy in every territorial dimension.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 293-301